System dynamics modeling of a knowledge management process: A case study in Turkish Airlines - TARIM, MEHVEŞ (ELSEVIER SCIENCE BV, 2013)
Tangible assets like land, machinery and equipment are crucial for an organization, while knowledge and intellectual capital are considered to be the primary source to complete an Organization. Knowledge management is defined as 'any practice of creating, acquiring, capturing, sharing and using knowledge to increase organizations' performance.' Knowledge management aims at managing positive and negative critical knowledge functions in different kinds of operations, identifying new strategies and new products, augmenting human resource management, and accomplishing number of targeted objectives or goals. Knowledge management process consists of four sets. These are creation or generation, storage or retrieval, transfer or sharing, and utilization. The main purpose of this study is to examine how the activities of knowledge management process and the variables excluded from knowledge management process interact with each other and how they affect organization performance by using system dynamics model specific case of Turkish airline. This study indicates that the activities of knowledge management process have a positive relationship with each other. There is also a positive relationship between these activities and organization performance.
Keywords: Knowledge management; Firm performance; System dynamics; Aviation industry; RESOURCE